The Relationship Between Filial Piety and the Academic Achievement and Subjective Wellbeing of Chinese Early Adolescents: The Moderated Mediation Effect of Educational Expectations - Guo, Xiaolin; Li, Junjie; Niu, Yingnan; Luo, Liang (Frontiers in Psychology, 2022)
A successful student has been defined as one who not only performs well in academics but is also happy. Hence, how to promote adolescents’ academic success and well-being is an important issue with which researchers have been concerned. A few studies have explored the relationship of filial piety to the academic achievement or life satisfaction of Chinese adolescents. However, in view of the close relationship between the two outcomes, the unique effects of filial piety on academic achievement and subjective well-being and their underlying mechanisms need to be further clarified. Based on a sample of 677 students in Grade 6 (Mage = 12.24, SD = 0.36) and their parents in Beijing, China, this study examines how adolescents’ reciprocal filial piety (RFP) and authoritarian filial piety (AFP) are related to their academic achievement and subjective well-being. It also examines the mediating role of adolescents’ educational expectations in these relationships, and the moderating role of parents’ educational expectations in the relationships of adolescents’ filial piety to educational expectations and of adolescents’ educational expectations to academic achievement and subjective well-being. The results indicate that, when the two outcome factors are considered simultaneously, RFP is positively related to academic achievement and subjective well-being. In contrast, AFP is negatively related to academic achievement but not significantly related to subjective well-being. Moreover, adolescents’ educational expectations play a mediating role in the relationships of both RFP and AFP to academic achievement and subjective well-being. In addition, the positive effect of adolescents’ educational expectations on subjective well-being is stronger when mothers’ educational expectations are higher, supporting the moderating role of parents’ educational expectations. Our findings provide new insights into and implications for the moderated mediation mechanism underlying the links between filial piety and early adolescent development.